An inter-disciplinary perspective on evaluation of innovation to support care leavers' transition. Issue 3 (31st July 2021) - Lynch, Amy; Alderson, Hayley; Kerridge, Gary; Johnson, Rebecca; McGovern, Ruth; Newlands, Fiona; Smart, Deborah; Harrop, Carrie; Currie, Graeme
Abstract : Purpose: Young people who are looked after by the state face challenges as they make the transition from care to adulthood, with variation in support available. In the past decade, funding has been directed towards organisations to pilot innovations to support transition, with accompanying evaluations often conducted with a single disciplinary focus, in a context of short timescales and small budgets. Recognising the value and weight of the challenge involved in evaluation of innovations that aim to support the transitions of young people leaving care, this paper aims to provide a review of evaluation approaches and suggestions regarding how these might be developed. Design/methodology/approach: As part of a wider research programme to improve understanding of the innovation process for young people leaving care, the authors conducted a scoping review of grey literature (publications which are not peer reviewed) focusing on evaluation of innovations in the UK over the past 10 years. The authors critiqued the evaluation approaches in each of the 22 reports they identified with an inter-disciplinary perspective, representing social care, public health and organisation science. Findings: The authors identified challenges and opportunities for the development of evaluation approaches in three areas. Firstly, informed by social care, the authors suggest increased priority should be granted to participatory approaches to evaluation, within which involvement of young people leaving care should be central. Secondly, drawing on public health, there is potential for developing a common outcomes' framework, including methods of data collection, analysis and reporting, which aid comparative analysis. Thirdly, application of theoretical frameworks from organisation science regarding the process of innovation can drive transferable lessons from local innovations to aid its spread. Originality/value: By adopting the unique perspective of their multiple positions, the authors' goal is to contribute to the development of evaluation approaches. Further, the authors hope to help identify innovations that work, enhance their spread, leverage resources and influence policy to support care leavers in their transitions to adulthood.